2017
DOI: 10.4049/jimmunol.1600064
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Induce Astroglial Differentiation and Migration of Human Neural Stem Cells via C1q and C3a Synthesis

Abstract: Inflammatory processes play a key role in pathophysiology of many neurologic diseases/trauma, but the effect of immune cells and factors on neurotransplantation strategies remains unclear. We hypothesized that cellular and humoral components of innate immunity alter fate and migration of human neural stem cells (hNSC). In these experiments, conditioned media collected from polymorphonuclear leukocytes (PMN) selectively increased hNSC astrogliogenesis and promoted cell migration in vitro. PMN were shown to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 94 publications
(128 reference statements)
6
43
0
Order By: Relevance
“…In comparison to rodent cells, hNSC require a longer time for in vitro differentiation. Our previous data suggest that a small proportion of hNSC remain uncommitted even after a 14 day in vitro differentiation period [15], however, evaluation of GFAP + cells in combination of stem cell markers Sox2 and Nestin indicates that by this timepoint GFAP expression correlates with astroglial lineage commitment rather than maintenance of neural progenitors [6]. After the last image acquisition at the 14 day timepoint, cells were fixed and triple-immunostained for lineage characterization using astroglial marker GFAP, oligodendroglial maker nuclear Olig2, or neuronal marker Map2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to rodent cells, hNSC require a longer time for in vitro differentiation. Our previous data suggest that a small proportion of hNSC remain uncommitted even after a 14 day in vitro differentiation period [15], however, evaluation of GFAP + cells in combination of stem cell markers Sox2 and Nestin indicates that by this timepoint GFAP expression correlates with astroglial lineage commitment rather than maintenance of neural progenitors [6]. After the last image acquisition at the 14 day timepoint, cells were fixed and triple-immunostained for lineage characterization using astroglial marker GFAP, oligodendroglial maker nuclear Olig2, or neuronal marker Map2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytes have a variety of functions, including formation and maintenance of neuronal synapses and the blood–brain barrier. However, many NS/PCs present in damaged CNS tissue differentiate into reactive astrocytes, which create a glial scar and, when in excess, likely contribute to a chronic inflammatory environment thought to prevent regeneration …”
Section: Introductionmentioning
confidence: 99%
“…However, many NS/PCs present in damaged CNS tissue differentiate into reactive astrocytes, which create a glial scar and, when in excess, likely contribute to a chronic inflammatory environment thought to prevent regeneration. [4][5][6][7][8][9][10] Over the past two decades, many studies have evaluated the therapeutic potential of transplanting human NS/PCs or oligodendrocyte progenitor cells (OPCs), the intermediary progenitors between NS/PCs and mature oligodendrocytes ( Fig. 1), to regenerate CNS tissues after injury.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence from the last two decades has demonstrated that C3aR is also expressed by many non-immune cells and participates in various physiological and pathological processes. For examples, C3aR signaling was reported to participate in the regulation of eye morphogenesis [16], neural development [17][18], embryonic chick retina [19] and cardiac resident cell [20] regeneration, astroglial cell differentiation [21] and survival [22], diet-induced obesity and metabolic dysfunction [23], and tau hyperphosphorylation in Alzheimer's Disease [24]. Also, C3aR signaling was found to be involved in the induction of in ammatory cytokines [25], proliferation of mesangial [11] and carcinoma cells [12] and EMT of tubular epithelial cells [10].…”
Section: Discussionmentioning
confidence: 99%